Factors Influencing Contraceptives Use among Women in the Juba City of South Sudan. (31st January 2018) - Obwoya, Justin Geno; Wulifan, Joseph K.; Kalolo, Albino
Abstract : Understanding birth control and child spacing methods used by inhabitants of conflict afflicted settings is important in designing interventions to improve uptake of family planning services. In addressing the dearth of knowledge on family planning use in these settings, this study aimed at identifying the influencing factors of contraceptives use among women in the Juba city of South Sudan. Using a population based cross-sectional study, 380 women aged 15–49 years filled a guided questionnaire between April and May in 2015. We collected contraceptive use data and factors influencing family planning uptake. Data analysis was performed using descriptive statistics and binary logistic regression. Lifetime reported contraceptive use stood at 42% whereas contraceptive use in the last three months was 36%. Logistic regression revealed attitudes (AOR = 1.375, 95 CI 1.246–1.518) and parity (AOR = 1.242, 95% CI 1.000–1.544) as significant determinants of lifetime contraceptive use whereas only attitude (AOR = 1.348, p < 0.001 ) determined contraceptive use in last three months. The findings indicate optimal uptake of family planning and point to the influence of attitudes and parity on contraceptive use. Changing attitudes and embedded sociocultural and political structures influencing attitudes is important to promote contraceptive uptake in these settings.